Evaluation of efficacy of two bag-mask ventilation techniques by novice airway providers: Two-handed CE versus dominant-hand CE–non-dominant-hand thenar eminence techniques – A randomised controlled trial - Neetu Saroye; Gurpreeti Kaur; Udeyana Singh; Anju Grewal; Akshita Khanna; Rushal Nayyar (Indian Journal of Anaesthesia, 2024)
Background and Aims: The conventional CE clamp technique may not effectively provide bag-mask ventilation (BMV) in the hands of inexperienced providers. Hence, we compared the efficacy of two-handed CE versus a hybrid technique. Methods: One hundred thirty-two American Society of Anesthesiologists (ASA) I–II adult patients were randomised into groups A and B. After induction of anaesthesia and neuromuscular blockade, Group A received BMV by using the double-handed CE technique. Group B received BMV by using dominant-hand CE and non-dominant-hand thenar eminence (TE) hybrid technique. The primary outcome was two minute (24 breaths) mean exhaled tidal volume. Secondary outcomes were the number of failed breaths and the comfortability level of airway providers using a 5-point Likert scale. Data were analysed using the Mann-Whitney U test, Student t-test, Chi-square test, and Fisher’s exact test. Results: The mean exhaled tidal volume and end-tidal carbon dioxide observed in Group A were significantly lower than in Group B (P = 0.001 and P = 0.001, respectively). The number of failed breaths and comfort level of both techniques were comparable in both groups (P = 0.310. and P = 0.584, respectively). Conclusion: The dominant-hand CE and non-dominant-hand TE techniques provide higher exhaled tidal volumes with comparable provider comfortability and may be considered an alternate BMV technique.